The Language and Identity of the Penan Muslims in KampongTanjong Belipat, Niah: A Preliminary Study - Shin, Chong (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
This article discusses the Penan Muslim community, which lives scattered around the Niah and Suai river valley in the northern part of Sarawak. In the past, they were a nomadic tribe that settled the remote areas in Sarawak and Kalimantan. Since the 19th century, some moved to the coastal area and embraced Islam as the religion of their community. The Penan Muslims in Tanjong Belipat village are one such community. After converting to Islam, the Penan Muslims abandoned their old traditional beliefs and also their mother tongue, the Penan language. Linguistically, the Penan language belongs to the Kayan-Kenyah language subgroup. After they embraced Islam, they adopted the Bintulu language-another language from the subgroup of languages in Northern Sarawak-as their main language. The Penan and Bintulu languages are mutually unintelligible. This kind of inter-group language shifting has a relation to religion, i.e. the Penan chose a language which they felt symbolizes a Muslim identity. Since the Bintulu tribe was the only Muslim tribe in the Niah valley, their language was chosen by the Penan as they adopted a new ethnic identity. After converting to Islam, the Penan Muslim community seems to have faced two complex yet subjective identities. Although they were now Muslim, they did not identify themselves as "Malay" like the Melanaus of Sarawak or the Dayak Muslims of Kalimantan. The term "Malay" was only used in certain circumstances and domains that are related to the economy. It is also observed that although the Penan Muslims are loyal to the Penan identity, intermarriage between them and the Malays has accelerated the "masuk Melayu" (becoming Malay) phenomenon among the Penan Muslim community. Keywords: Penan, Penan Muslims, Islam, language, identity, becoming Melayu